Pengaruh Metode Latihan Drill Shooting dan Latihan Media Target Terhadap Akurasi Shooting Sepak Bola Atlet SSB Keeltjes Soccer Academy U-12 Tahun - Kurnianto, Seida; Puriana, Ramadhany Hananto; Wahyono, Muhammad; Suryansah, Suryansah; Aryanto, Sherif Juniar (Jurnal Porkes, 2025)
The purpose of this study is to examine which is more influential than the drill shooting training method and target media training on shooting accuracy in SSB Keeltjes Soccer Academy U-12 athletes. The research method used is descriptive quantitative. The design used two group pretest and posttest design. The population of this study was 90 athletes who attended SSB Keltjess Soccer Academy aged 12 years. The sample of this study was 20 athletes. To analyze the data using the prerequisite test using SPSS 26. The result is a sig value based on mean 0.383> 0.05, concluded homogeneous data. The shooting drill group sig. (2 tailed) 046 > 0.05 then Ho is accepted, it is concluded that there is no difference in the average results of pretest drill shooting with posttest drill shooting which means there is no effect of drill shooting training on shooting accuracy. Target media group sig. (2 tailed) 0.00 <0.05, then Ha is accepted, it can be concluded that there is an average difference in the pretest results of the target media group with the posttest of the target media group, which means that there is an effect of target media training on shooting accuracy. In conclusion, the 2 groups, namely the drill shooting group and the target media, that target media training is one of the exercises that is effective enough to improve shooting accuracy.